2007
DOI: 10.1007/s00232-007-9071-7
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel

Abstract: We used patch-clamp techniques and A6 distal nephron cells as a model to determine how cholesterol regulates the renal epithelial sodium channel (ENaC). We found that luminal methyl-beta-cyclodextrin (mbetaCD, a cholesterol scavenger) did not acutely affect ENaC activity at a previously used concentration of 10 mM: but significantly decreased ENaC activity both when the cell membrane was stretched and at a higher concentration of 50 mM: Luminal cholesterol had no effect on ENaC activity at a concentration of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…In four similar recordings the single channel conductance calculated for the reduced and the full channel openings averaged 3.04 ± 0.11 pS and 5.71 ± 0.04 pS (n=4, N=2), respectively. Our observation that MβCD pretreatment may cause the appearance of ENaC conductance sublevels in at least some of the patches is in good agreement with a recent report that ENaC subconductance events were observed in A6 cells after treatment with 50 mM MβCD [49]. Collectively, our findings indicate that cholesterol removal has significant effects on the single channel properties of ENaC.…”
Section: Effect Of Cholesterol Removal On Single Channel Properties Osupporting
confidence: 82%
See 1 more Smart Citation
“…In four similar recordings the single channel conductance calculated for the reduced and the full channel openings averaged 3.04 ± 0.11 pS and 5.71 ± 0.04 pS (n=4, N=2), respectively. Our observation that MβCD pretreatment may cause the appearance of ENaC conductance sublevels in at least some of the patches is in good agreement with a recent report that ENaC subconductance events were observed in A6 cells after treatment with 50 mM MβCD [49]. Collectively, our findings indicate that cholesterol removal has significant effects on the single channel properties of ENaC.…”
Section: Effect Of Cholesterol Removal On Single Channel Properties Osupporting
confidence: 82%
“…This is in good agreement with recent findings [7] that membrane cholesterol extraction did not significantly affect the electrophysiological parameters of A6 renal epithelial cells under steady-state conditions. Some studies suggested that a high cholesterol content of the plasma membrane tends to stabilize ENaC function [49]. In contrast, reducing plasma membrane cholesterol was reported to impair ENaC function but with rather variable effects [7,8,49,52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ROMK1, ENaC is also regulated by cholesterol 34,35 and PI(4,5)P 2 . [36][37][38] However, unlike ROMK1 channels, ENaC appears to be localized in microvilli.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ENaC is proposed as the key mediator of aldosterone-dependent BP control in the endothelium [80] . Several studies, in different cell types including CCD and endothelial cells, have suggested that ENaC may function as a mechanosensor and that mechanical stimuli may activate ENaC [22,81,82] . Because endothelial ENaC inhibition may activate nitric oxide (NO) synthase [83] , it is completely possible that altered blood flow (shear stress), which is caused by over reabsorption of Na + via ENaC located at distal nephron, may affect the NO production in endothelia.…”
Section: The Molecular Variations In Enac and The Risk For Developingmentioning
confidence: 99%